THE ANALYSIS OF WASTE GENERATION AND WASTE COMPOSITION IN PRESIDENT UNIVERSITY, CIKARANG, INDONESIA - Fifi Indriyani; Filson M. Sidjabat (President University, 2020)
Abstract. Waste is an environmental problem that is the concern of everyone, increasing the volume of waste every year produced from the source. President University is one of the source that is still use the old paradigm in waste management makes President University continues to be one source that can increase the volume of waste that will be disposed of to landfill. This is reinforced by the increasing number of students each year. Therefore, as a role model from education level, proper waste management is needed. Objectives: Based on that, the objective of this research is to describe the existing condition of waste management at President University and to measure the waste generation and waste composition as baseline data for amount of dustbin and temporary waste collection area needed. Method and results: The Method implemented in this research using SNI 19-3964-1994 standard. The result showed that the total of waste generation at President University reached 238 gr/day/person with a total of 14% compostable waste, 31% recyclable waste, and 55% residue. Conclusion: It was suggested to plan and operate dustbin that following its types with the color-coded for different types of waste generation in President University. Also, recommend some alternative treatment ideas such as composting or anaerobic digester for treatment the waste.